2014
DOI: 10.1001/jamaneurol.2014.1584
|View full text |Cite
|
Sign up to set email alerts
|

Triheptanoin for Glucose Transporter Type I Deficiency (G1D)

Abstract: IMPORTANCE Disorders of brain metabolism are multiform in their mechanisms and manifestations, many of which remain insufficiently understood and are thus similarly treated. Glucose transporter type I deficiency (G1D) is commonly associated with seizures and with electrographic spike-waves. The G1D syndrome has long been attributed to energy (ie, adenosine triphosphate synthetic) failure such as that consequent to tricarboxylic acid (TCA) cycle intermediate depletion. Indeed, glucose and other substrates gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 72 publications
2
36
0
Order By: Relevance
“…Our study provides a comprehensive overview of the variety of symptoms associated with GLUT1DS and their variability with age. Consequently, our data underlines the considerable delay in diagnosing the disease (even considering that mutational analysis was available since 1998 [Seidner et al, 1998] in our cohort only 6 patients exhibited symptoms before 1998, thus the median delay between 1998 and the age at diagnosis, was still 6 years (12 months-11years 7months)), when a potential treatment can be proposed with KD, and maybe in the future other potential treatments [Pascual et al, 2014]. Prior studies have emphasized the wide range of epilepsies associated with GLUT1DS [Arsov et al, 2012a[Arsov et al, , 2012bMullen, 2011;Mullen et al, 2010;Pong et al, 2012;Striano et al, 2012;Suls et al, 2009].…”
Section: Discussionmentioning
confidence: 75%
“…Our study provides a comprehensive overview of the variety of symptoms associated with GLUT1DS and their variability with age. Consequently, our data underlines the considerable delay in diagnosing the disease (even considering that mutational analysis was available since 1998 [Seidner et al, 1998] in our cohort only 6 patients exhibited symptoms before 1998, thus the median delay between 1998 and the age at diagnosis, was still 6 years (12 months-11years 7months)), when a potential treatment can be proposed with KD, and maybe in the future other potential treatments [Pascual et al, 2014]. Prior studies have emphasized the wide range of epilepsies associated with GLUT1DS [Arsov et al, 2012a[Arsov et al, , 2012bMullen, 2011;Mullen et al, 2010;Pong et al, 2012;Striano et al, 2012;Suls et al, 2009].…”
Section: Discussionmentioning
confidence: 75%
“…A small scale open-label case series tested the effects of triheptanoin-supplemented diets in 14 patients with inborn glucose transporter type I deficiency. The authors of this study reported a modest improvement in ictal events, but the underlying mechanisms were not further evaluated [20]. Branched octanoic acid compounds have been generated that show promising antiseizure activity in in vitro and in vivo seizure models, without affecting histone deacetylase activity [21].…”
Section: Medium-chain Fatty Acidsmentioning
confidence: 99%
“…The ability of triheptanoin to provide both acetyl-CoA and propionyl-CoA makes it an ideal metabolic treatment for disorders with deficient levels of TCA cycle intermediates and impairments in energy production. For instance, triheptanoin alleviated metabolic disturbances associated with several neurological and neuromuscular disorders and improved symptoms in models of epilepsy (Willis et al, 2010; Thomas et al, 2012; Hadera et al, 2014), Canavan disease (Francis et al, 2014), autism disorders (Park et al, 2014) and Alzheimer's Disease (Aso et al, 2013) as well as patients and a mouse model of glucose transporter 1 deficiency (Marin-Valencia et al, 2013; Pascual et al, 2014; Mochel et al, 2016), and patients with Huntington's disease (Mochel et al, 2010; Adanyeguh et al, 2015). In chronically “epileptic” mice it was shown that triheptanoin partially restores reduced TCA cycle intermediate and metabolite levels (Willis et al, 2010; Hadera et al, 2014).…”
Section: Metabolic Treatments In Alsmentioning
confidence: 99%